Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Guru di SMA Negeri 14 Kabupaten Gowa - Muh Priyo Wicaksono; Edi Jusriadi; Muchriady Muchran (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the influence of work motivation and work environment on teacher performance at SMA Negeri 14 Gowa. This study uses a quantitative approach with a type of causal associative research. The population in this study is all teachers of SMA Negeri 14 Gowa which is 56 people with saturated sampling techniques so that the entire population is used as a research sample. Data collection was carried out through a questionnaire with a Likert scale. The data analysis method used was multiple linear regression analysis with the help of the IBM SPSS program. The results of the study show that work motivation and work environment have a positive and significant effect on teacher performance. This shows that the higher the work motivation and the better the work environment, the teacher's performance will also increase. In addition, this study also shows that a conducive work environment is able to strengthen teachers' morale in carrying out learning tasks optimally. This finding is expected to be the basis for schools to improve the quality of teacher performance through better motivational management and work environment.